Pre-treatments effect on the tetrazolium test on Epidendrum barbaricum Hágsater & Dodson seeds (2020)
Orchids are affected by several factors that impair their spreading, which is necessary to know the viability of their seeds. The aim of this research was to determine the most suitable preconditioning treatment to potentiate the tetrazolium test in Epidendrum barbaricum seeds. Initially, the mature capsules were collected near the city of Pasto in the Department of Nariño (Colombia), and seeds were obtained. Subsequently, the seeds were submitted to four pretreatments: immersion in distilled water, 1% hypochlorite, 10% alcohol and 10% sucrose. Seeds were then rinsed with distilled water and exposed to two concentrations of 2,3,5-trifenyl tetrazolium chloride (0.25%, 1%) and different exposure times (6, 12, 24, and 48 hours). To perform the tests, the 5 ml syringe with cloth filter method was used. The viability test results were corroborated with the in vitro germination test, using the MS (Murashige and Skoog) culture medium. The most reliable viability findings (93%) were obtained by using preconditioning with sodium hypochlorite, a value that has a high correlation with the percentage of germination (93%), independent of the tetrazolium concentration at an exposure time of 24 hours